Machine learning In breast cancer prognosis and prediction - Chowdhury, Shah Abul Hasnat; Faruqee, Golam Akbar; Hassan, Sayeed; Jawad, Golam Mostafa Chowdhury (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.